Analysis of inequalities in access to healthcare in North-east Portugal - Sara Reis; Emanuela Maldonado; João Matos de Barros; Afonso Aroso Louro; Manuel Guimarães; Bárbara Barroso; Hélder Fernandes; André Novo (Cadernos de Saúde)
Introduction: Healthcare accessibility stands as a multifaceted challenge, intricately woven with factors ranging from geographical location to economic status. Mental health, an indispensable aspect  of overall well-being, is particularly susceptible to the inadequacies pervasive within global healthcare systems. Against this backdrop, schizophrenia emerges as a poignant example of the profound challenges faced by individuals navigating mental health disorders within healthcare systems. In  the context of Portugal, while strides have been made in recognizing healthcare equity as a fundamental right, persistent regional disparities persist, underscoring the imperative for a coordinated effort to bridge these gaps. The interplay between geographical barriers and healthcare accessibility manifests as a critical determinant of health outcomes, particularly poignant in rural and remote communities where access to  specialized care remains elusive. Objective: This article aimed to analyse the characteristics of the schizophrenia spectrum disorder population in the Bragança district and the disparities in their healthcare access. Methods: A cross-sectional, descriptive study was conducted on a sample of 274 patients provided by the Mental Health Department at the Unidade Local de Saúde Nordeste (ULSNE – Northeast Local Healthcare Unit), for sociodemographic characterization. The data were retrieved from the hospital’s database. The study was approved by the Ethics Committee of the Polytechnic Institute of Bragança. Results: The research enrolled 274 individuals diagnosed with schizophrenia, predominantly male (65.7%), with most falling within the 40-49 and 50-59 age brackets. Hospitalization frequency averaged 4.73 ± 6.74 instances, with men exhibiting higher rates. A significant correlation was found between medical monitoring and hospitalization frequency, particularly among patients with follow-up. Moreover, a notable discrepancy in healthcare  accessibility was identified across municipalities, necessitating considerable patient travel for psychiatric consultations. Conclusion: The case study examined the challenges faced by patients diagnosed with schizophrenia spectrum disorders in the Bragança district. These findings highlight the urgent need for improvements in the existing healthcare infrastructure, including the expansion of medical services in underserved areas and the implementation of innovative solutions such as telemedicine.